1998
DOI: 10.1080/02791072.1998.10399674
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Methadone Maintenance: Implications for HIV Prevention

Abstract: Attitudes of opioid users toward methadone maintenance were studied using semi-structured field interviews. One hundred and sixty-one heroin and speedball users in San Antonio, Texas, were interviewed between 1989 and 1992. Users were classified according to whether or not they had ever been on methadone maintenance. Opioid users who had never been on methadone maintenance were more likely to express a negative attitude toward methadone maintenance than users who had been on it (50% versus 30%). Sources of neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…While problematic patients may be evident outside many clinics, the more successful patients are invisible, often concealing their treatment from friends, employers, and even physicians. 12,14 Thus, misunderstandings among patients, the misuse of methadone by providers, the burdensome regulation of treatment, and the stigma that serves to hide the successes of MM all combine to impede the goal of expanding methadone maintenance treatment to prevent HIV and decrease the harms of substance abuse. The NIH Consensus Development Conference found that the median mortality of methadone-maintained patients was 30% that of untreated patients, and that the financial burden of untreated heroin addiction is as great as $20 billion per year.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While problematic patients may be evident outside many clinics, the more successful patients are invisible, often concealing their treatment from friends, employers, and even physicians. 12,14 Thus, misunderstandings among patients, the misuse of methadone by providers, the burdensome regulation of treatment, and the stigma that serves to hide the successes of MM all combine to impede the goal of expanding methadone maintenance treatment to prevent HIV and decrease the harms of substance abuse. The NIH Consensus Development Conference found that the median mortality of methadone-maintained patients was 30% that of untreated patients, and that the financial burden of untreated heroin addiction is as great as $20 billion per year.…”
Section: Introductionmentioning
confidence: 99%
“…These concerns have been documented in the literature for many years. [10][11][12][13][14] Patients believe that methadone is more damaging to health than heroin; specifically, the popular understanding is that it damages bones and teeth, and that achieving withdrawal from it is almost impossible. Even methadone providers misunderstand the roles of adequate dosing and long-term maintenance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, lack of adherence to clinical practice guidelines might stem from identified barriers such as lack of faith in the results of randomized clinical trials, negative community attitudes regarding OST, philosophical opposition to treating Bdrug addiction with drugs^, administrative and pharmacy/ formulary barriers at the facilities where the clinics are operating, lack of staff, qualified prescribing clinicians, or funding, low demand or priority, lack of confidence in effectiveness, [21][22][23] or patient preferences concerning methadone treatment. 24,25 If barriers limit guideline adherence, and guideline adherence is important for optimizing treatment outcomes, then treatment outcomes at clinics that more strictly adhere to clinical practice guidelines should be superior.…”
Section: Introductionmentioning
confidence: 99%
“…The most important reason is likely the lack of adherence to best practices and clinical guidelines in prescribing MMT, with many patients receiving less than the minimum effective maintenance dose of 60 mg per day [29]. Other reasons include difficulties with side effects such as nausea, numbness, severe withdrawal, and depression, and the poor street reputation of MMT among some drug users [30,31]. Alternative treatment modalities are needed for opioid-dependent individuals who cannot be attracted into or productively retained in conventional forms of opioid-addiction treatment.…”
Section: Methadone Maintenance Treatment (Mmt)mentioning
confidence: 99%